BUSINESS STRATEGIES TO SUSTAIN IN GLOBAL MARKETPLACE (Conferencea, 2022)
The primary goal of this research is to examine how glocalization strategies assist businesses in creating long-term marketing positions. The paper will also discuss why some companies had to switch to the glocalization plan after the initial globalization "one-size-fits-all" strategy failed. What strategic methods, and techniques have businesses used to get through crises. Additionally, the effectiveness of the glocalization strategy will be evaluated in terms of how well it contributes to overall success. The paper will draw on the marketing management analysis such as SWOT. At the conclusion of the report, suggestions will be given based on the findings of the analysis.